Exploring Emerging Trends in Phonetics: The Influence of Orthographic Forms and Technological Integration in Language Learning - Reflinda, Reflinda; Veni Roza; Firdaus, Fatimah (REiLA : Journal of Research and Innovation in Language, 2024)
Phonetics, a crucial aspect of linguistics, plays a significant role in language acquisition and proficiency. This systematic literature review investigates emerging trends in phonetics research from 2019 to 2024, focusing on the impact of orthographic forms on second language (L2) phonological representation and processing. Utilizing tools like Publish or Perish, with database Crossreff (1000), Google Schoolar (230) and Scopus (26) and total 1256 (n=26) studies to explore how orthographic inputs affect L2 learners' speech perception, production, phonological awareness, and lexical learning. Our findings reveal that orthographic forms can override phonological inputs, leading to persistent effects despite extensive exposure and formal teaching. This study highlights the necessity of incorporating orthographic considerations into phonetic and phonological instruction to enhance L2 learning outcomes. Furthermore, it examines the role of technology, such as YouTube and AI-driven platforms, and innovative pedagogical strategies, including embodied cognition, in improving phonetic education. By aligning with similar studies, this research reinforces the pervasive influence of orthography on L2 phonological development and underscores the importance of developing comprehensive teaching strategies. In the larger context, these findings contribute valuable insights to the field of phonetics and language education, emphasizing the need for tailored educational methods that address orthographic influences, ultimately leading to more effective language learning practices globally. Future research should explore a wider range of languages and orthographic systems, employing longitudinal and experimental designs to deepen the understanding of orthographic effects on phonological development.